Understanding Teachers' Beliefs, Professional Dispositions, Orientation towards Technology and Technology Use in South African Secondary Schools: A Longitudinal Micro-, Meso- and Meta-Theory Perspective - Matthee, Machdel C. (University of Pretoria, 2022)
Thesis (PhD (Information Systems))--University of Pretoria, 2021.